Penerapan Quick Response (QR) Code Berbasis Web Di Puskesmas Payung Sekaki Pekanbaru - Ken Rio Agizki; Regiolina Hayami; Harun Mukhtar (Universitas Muhammadiyah Riau, 2020)
Puskesmas staffing data certainly cannot be separated from data that can change at any time. Changes to the data must be stored properly. At Puskesmas Payung Sekaki the attendance system is still using paper as an employee attendance data file, so that frequent loss of data and double data on absenteeism makes mistakes for the staffing of Puskesmas Payung Sekaki. Supporting Puskesmas staff every day must go to the Puskesmas to attend attendance when they come and go home, so that fraud arises in making attendance by making attendance care.Attendance system using the QR Code, can easily search data and minimize fraud in attendance care, because the QR Code must scan. The QR Code scanning results will be saved in the database. The QR Code is made with the Puskesmas Employee Identification Number. The results obtained from the Implementation of the Quick Response (QR) Code for the attendance of Puskesmas are able to facilitate employees in making attendance and the head of administration to get information on the attendance of Puskesmas Payung Sekaki employees.